DI-080 Successful treatment and prevention of cisplatin/etoposide induced encephalopathy with thiamine. (14th February 2016) - Langebrake, C; Reintjes, A; Goertitz, I; Rutkowski, S; Von Hugo, A
Abstract : Background: Cytostatic drugs that typically may cause encephalopathy comprise methotrexate and ifosfamide. For cisplatin, neurotoxicity is a common adverse effect, mainly limited to axonal sensory neuropathy, but CNS disorders have also been reported. Purpose: To present a patient with symptoms of encephalopathy while receiving chemotherapy with cisplatin and etoposide and the successful treatment and prophylaxis with thiamine. Material and methods: A 9-year-old male patient with neuroblastoma stage 4 was treated according to the trial NB2004-HR. Chemotherapy consisted of alternate application of vindesin/cisplatin/etoposide (N5) and vincristine/dacarbacine/ifosfamide/doxorubicine (N6) at intervals of 3 weeks for a total of three cycles each. During his first N6 cycle, he developed ifosfamide induced encephalopathy with symptoms of confusion, disorientation and slurred speech, which was successfully treated with thiamine. During the second N5 cycle, the symptoms recurred, and after review of the literature and discussion, it was decided to prescribe thiamine (75 mg every 6 h). The symptoms resolved immediately. During the following N5 and N6 cycles, the patient was prophylactically treated with thiamine and no signs of central neurotoxicity were observed. Retrospectively, during the first N5 cycle, milder symptoms of encephylopathy did also occur. Results: Employing widely accepted causality scales for adverse effects (Naranjo scale or WHO-UMC causality categories), it was probable that cisplatin (Naranjo score 6, WHO-UMC probable/likely) or etoposide (Naranjo score 5 points, WHO-UMC probable/likely) caused the encephalopathy. Several aspects support thiamine's efficacy: (1) reasonable time relationship of adverse neurologic symptoms to N5 cycle, (2) effect is unlikely to be explained by other drugs and (3) response to thiamine was reasonable. As we did not withdraw thiamine in one of the following N5 cycles, it was not possible to evaluate whether the symptoms would have reappeared without thiamine, which would further corroborate our hypothesis. Conclusion: To our knowledge, this is the first report of successful use of thiamine against non-ifosfamide induced encephalopathy. Thiamine might provide a reasonable option for the treatment and prevention of cisplatin/etoposide induced encephalopathy in children with neuroblastoma. No conflict of interest.